2021
DOI: 10.4239/wjd.v12.i12.2096
|View full text |Cite
|
Sign up to set email alerts
|

Sodium ozagrel and atorvastatin for type 2 diabetes patients with lacunar cerebral infarction

et al.

Abstract: BACKGROUND The main pathological factor of cerebral infarction is atherosclerosis, which is the pathological process of chronic inflammatory diseases such as vascular smooth muscle hyperplasia, inflammatory cell infiltration, extracellular matrix increase, and thrombosis. At present, the focus of clinical treatment is anti-platelet aggregation and improving blood status, and current research is limited to improving symptoms only. AIM To observe the effect of sodium ozag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Subsequently, the investigation results of clinical efficacy showed a higher response rate in AP + ATO group compared with ATO group, suggesting that AP + ATO has a more significant therapeutic effect on CA. Yu Y, et al also pointed out that AP has a certain improvement effect on cerebral thrombosis [ 15 ], which can also corroborate the results of this experiment and once again demonstrate the excellent application potential of AP in CA treatment. Furthermore, when comparing the changes of BP and blood lipids, we found that the BP improvement of patients in the study group was more significant, which also shows that AP + ATO is more suitable for EH patients with CA.…”
Section: Discussionsupporting
confidence: 87%
“…Subsequently, the investigation results of clinical efficacy showed a higher response rate in AP + ATO group compared with ATO group, suggesting that AP + ATO has a more significant therapeutic effect on CA. Yu Y, et al also pointed out that AP has a certain improvement effect on cerebral thrombosis [ 15 ], which can also corroborate the results of this experiment and once again demonstrate the excellent application potential of AP in CA treatment. Furthermore, when comparing the changes of BP and blood lipids, we found that the BP improvement of patients in the study group was more significant, which also shows that AP + ATO is more suitable for EH patients with CA.…”
Section: Discussionsupporting
confidence: 87%
“…The research group treated with ATO+ASP also showed higher ADL and lower NIHSS after treatment, indicating that combined treatment can significantly improve patients' ADL ability and reduce neurological deficits. In the research of Yu et al ATO+sodium ozagrel not only significantly inhibits inflammatory reactions in patients with type 2 diabetes mellitus complicated with lacunar infarction, but also alleviates neurological deficits, similar to our findings [24] . Another study reported that ATO calcium plus ASP is not only better than ASP alone in the treatment of patients with acute ischemic stroke, but also contributes to a lower incidence of complications and shorter hospitalization time, as In this study, the efficacy was compared between the conventional group receiving ASP therapy and the research group receiving ATO+ASP.…”
Section: Resultssupporting
confidence: 91%
“…T2DM is a prevalent metabolic disease that is often accompanied by abnormal lipid metabolism and contributes to cerebrovascular diseases such as cerebral infarction ( 117 ). Recent research has shown that the combination of sodium ozagrel and atorvastatin can effectively reduce the inflammatory response, regulate HMGB1 levels, and regulate blood glucose and lipid levels in patients with T2DM and lacunar infarction ( 118 ). Another complication that commonly arises in diabetic patients is DN.…”
Section: Regulating Hmgb1 To Treat Diabetesmentioning
confidence: 99%